A Generalized Subclass of Starlike Functions Involving Jacksonâ€™s ( p, q) ï€ Derivative - Yousef, Abdeljabbar Talal; Salleh, Zabidin (Iraqi Journal of Science, 2020)
In this paper, we generalize many earlier differential operators which were studied by other researchers using our differential operator. We also obtain a new subclass of starlike functions to utilize some interesting properties.